PERSENTASE KASUS TRIPLE NEGATIVE BREAST CANCER DI RUMAH SAKIT UMUM PUSAT (RSUP) SANGLAH TAHUN 2006-2013: STUDI DESKRIPTIF - Wedari, Ni Luh Putu Harta; Sudarsa, I Wayan (E-Jurnal Medika Udayana, 2015)
TRIPLE NEGATIVE BREAST CANCER CASE PERCENTAGE AT SANGLAH GENERAL HOSPITAL IN THE YEAR OF 2006-2013: A DESCRIPTIVE STUDY   World Health Organization predicts that there will be a surge in breast cancer patients in Indonesia up to seven times by 2030. Bali Province ranked second highest breast cancer patients diagnosed in Indonesia, which is based on the data in Sanglah General Hospital, every year there were 200 new cases. This research is a descriptive study with secondary data of triple negative breast cancer inpatients in the Department of Surgical Oncology, Sanglah General Hospital from 2006 until 2013. The percentage of triple negative breast cancer case is 14,28 %, 32%, 75 % in 2007, 2008, and 2009 respectively. Number of cases continued to rise in 2010 amounted to 51.85 %, then decreased in 2011 to 16.67 % but no cases in 2013. Most age groups diagnosed as triple negative breast cancer is 41-45 years which the bigest percentage is 33.34%. The number of triple negative breast cancer among other types of breast cancer has increased with the most age groups diagnosed is 41-45 years old.
Keywords: Triple negative breast cancer